Being There Even When You Are Not: Presence in Distance Preaching - Sensing, Tim (Religions, 2023)
Listening to sermons through digital media is not new. However, the pandemic pressed many preachers into a medium in unexpected ways. The need for immediate solutions did not allow time for preachers to reflect on what was happening theologically. This paper explores theological presence. The question of how one creates connection and presence when no one is even in the same room, city, or country is not a new one. The rhetorical concern of being “present while absent” shows up in the writings of ancient rhetoricians, opening the door for theological conversation. Recognizing there are ways to employ rhetorical techniques for non-virtuous ends, the pandemic also exposed that some virtuous attempts also failed the ecclesial need to build relationships online. Digital platforms and social media give churches and ministers opportunities to hold space for developing relationships and witnessing the Gospel.